Tinjauan Literatur Tentang Perubahan Saluran Pemasaran Kopi: Tantangan Dan Peluang di Era Digital - M. Egitia Zaini; Meodina Syafitri Daulay; Hanivatul Husna; Wien Kuntari (JURNAL ILMIAH NUSANTARA, 2024)
Arabica coffee (coffea arabica) is a type of coffee that is very popular throughout the world and is the basic ingredient for coffee drinks that are widely consumed. To reach consumers, efficient marketing is needed, such as using digital marketing strategies. Arabica coffee through digital marketing helps farmers directly reach end consumers. This journal analysis aims to provide an overview of the opportunities and constraints of coffee marketing channels in the current digital era. The method used is the literature study method or literature study. The analysis stages of this literature study include (1) data collection, (2) data filtering to find relevant journals, (3) understanding and presenting the data in the form of a literature and review. The literature and review results obtained show that the market development strategy for making marketing channels efficient for farmers is carried out online by utilizing digital media through e-commerce and social media such as Instagram, WhatsApp and Facebook so that farmers can have direct contact with end consumers.